Aragonesisms in a "Judicial Dictionary" of 1831 - López Susín, José Ignacio (Revista de derecho aragonés, 2025)
A reference by Professor Jesús Delgado in the preface to the book Marceliano Isábal y su «Diccionario del Derecho Aragonés» prompted an investigation into a judicial dictionary published in the first third of the 20th century. The dictionary, attributed to an anonymous author identified only by initials, includes various Aragonese terms. This study aims to trace the sources used in the dictionary and determine the identity of its author.
Keywords: dictionary; Aizquíbel; Basque; Real Academia Española; Aragonese